THE MEDIATING ROLE OF FINANCIAL PERFORMANCE IN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) AND FIRM VALUE - Putra, Fajar Karunia; Budastra, Made Aditya (Jurnal Akuntansi Bisnis, 2024)
Background: As global awareness begins to lead to sustainable business practices, the Environmental, Social, and Governance (ESG) framework becomes one of the important things in evaluating firms. Sustainability information such as ESG is considered capable of influencing firm value.Objective: The goal of the study is to examine the effect exerted by ESG on the value of the firm with financial performance acting as a mediating variable.Research Method: This study utilizes regression data analysis techniques to test the influence between variables. Secondary data were used in this study using Thomson Reuters and OSIRIS databases. The sample obtained was 35 firms that fit the purposive sampling criteria, with the number of observations for the 2017-2022 period being 210 observations.Research Results: ESG cannot affect firm value, while ESG can affect financial performance, and financial performance can affect firm value. Results also show the full mediating effect exerted by financial performance on the connection between ESG and firm value.Research Originality/Novelty: A research construct that uses financial performance mediation in explaining the connection between ESG and firm value.